The Implemention of Describing Pictures Strategy in Improving Students Speaking on the Desciriptive Text Ability in SMP Abbasyiah NW Jerua - Zulsapikri, Wiranto; Usuluddin; Yusri, Ahmad; Fikni, Zahratul (Innovative: Journal Of Social Science Research, 2024)
This research aims to determine the effect of using image media on students' learning and English speaking skills. This research was carried out at Abbasyiah NW Jerua Middle School, West Sakra District, East Lombok Regency. This research uses quantitative research, applying pre-experimental research to determine the speaking abilities of Abbasyiah NW Jerua Middle School students. To determine students' abilities, researchers used pre and post-tests. The test aims to measure students' ability to speak before and after being given treatment. The research results show an increase in student learning outcomes through the use of image media. This can be seen from the increase in pretest-posttest results given before and after treatment. From the results of the pretest and posttest carried out on students, the average score was 46.39 for the pretest and 91.39 for the posttest. And the results of the hypothesis test show that the hypothesis that has been formulated is accepted (Ho is accepted, while Ha is rejected) which means there is a significant difference in the use of image media in improving students' speaking skills in the English learning outcomes of Abbasyiah NW Jerua Middle School students.